STUDI ANALISIS PELAYANAN ADMINISTRASI, AKADEMIK, FASILITAS MAHASISWA TERHADAP KEPUASAN ALUMNI ILMU ADMINISTRASI NEGARA FISIP-UNDANA - Made N D Andayana (Journal of Management Small and Medium Enterprises (SMEs), 2020)
Higher education management refers to the five pillars of quality, autonomy, accountability,accreditation and evaluation (Dirjen Dikti, 1990), the ultimate goal of continuous qualityimprovement. Management improve the quality of higher education is defined as a professionalpublic service that is run and directed as much as possible to provide services that are in accordancewith the standards or more. In an effort to find out customer satisfaction in this case is the alumni ofthe Undana FISIP State Administration Study Program on service quality as measured by theinfluence of Alumni Satisfaction on Administrative Services, Academic Services and StudentFacility Services. According to the results of this study, adequate administrative services, adequateacademic services and unsatisfactory facility services. The relationship of simple correlation andshows the relationship between administrative services with academic services to the satisfaction ofalumni classified as moderate or quite satisfying alumni. Suggestions from the research team,services that are categorized as providing administrative and academic satisfaction to be maintainedand continue to be even better and improved, while our facility services the research team hopes toget special attention from the institution. Keywords: Alumni Satisfaction, Administrative Services, Academic Services, Student FacilityServices